Morphobiological features and productivity of artichoke in the conditions of Southern Uzbekistan - M. N. Aramov; B. N. Aliyev (Овощи России)
Relevanc and methods. The article presents the research results on the introduction of artichoke in Uzbekistan. In the process of research, some issues of artichoke seed production in the conditions of dry subtropics of Uzbekistan were also studied. Studies were carried out on the Krasavets cultivar. When identifying the most effective method for forming a seed bush, the comparison of growing seed plants without formation and 4 methods of formation was compared: 1 stalk on a plant and 3 inflorescences on a stalk, 2 stems on a plant and three inflorescences on each, 3 stems on a plant and three inflorescences on each, 4 stems on the plant and three inflorescences on each. Results.It was revealed that artichoke plants grow and develop, form full-fledged seeds during the growing season. The manifestation of morphobiological and economically valuable traits largely depends on the age of the plants. A significant reduction in the growing season, an increase in the height of plants and the number of stems, an increase in the average mass and number of inflorescences and, ultimately, yield occurs in the second year of plant life. It was also revealed that the potential productivity of artichoke plants in Uzbekistan is very high. The yield of the Krasavets cultivar in the second year of life is 55.5 t/ha, and that of the Green Globe cultivar is 39.2 t/ha. This is significantly higher than the global average. The highest seed productivity was noted in the variant without the formation of a seed plant: 734.2 g/plant or 15789 seeds/plant. However, in such indicators as the mass and number of seeds from one inflorescence, the mass of 1000 seeds of a plant without formation is significantly inferior to other options. Based on the results of experiment 3, 4, 5, the options can be considered appropriate to use in artichoke seed production.